THE IMPACT OF COACHING AND MENTORING ACTIVITIES TOWARDS DECREASING CREATIVE IDEAS OF GEN Y EMPLOYEES IN MEDIA COMPANY - Zahara Tussoleha Rony (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This study aims to analyze and describe an event of declining creative ideas in media companies in 2014-2015 is associated with the implementation of coaching and mentoring activities of production division employees in 2014-2015. Research uses qualitative method. Data obtained from field observation, documentation study and interview to 20 informants. Their production employees have worked for at least 3 years and are classified as Gen Y. Along with the change of leader, coaching and mentoring activities conducted by long-time leaders are much reduced. Activities such as establishing trustworthiness, actively listening, clarifying, asking questions, giving feedback are not effective yet. Not all leaders have opened the initial conversation well. The listening activity has not been fully accompanied by empathy. Questioning and feedback activities have not fulfilled the rules of coaching and mentoring. The results of this study showed that most new leaders have not mastered and implemented effective coaching and mentoring skills and even have not realized the decline in these activities has had an impact on the decline of creative ideas. Keywords: Coaching, Gen Y, Leader, Mentoring